Manejo contable y tributario de Refrescos Sin Gas S. A. Agencia Babahoyo en los periodos 2020 y 2021. - Manzaba Troya, Elena Del Roció (2022)
This case study is based on the profitability, accounting management and tax contribution to the company Refrescos Sin Gas S.A. regarding the periods 2020 and 2021; This organization belongs to the private sector, created for profit, regulated under the control of the Superintendence of Securities and Insurance Companies, has several branches, however in this project it will be limited to studying the branch located in the city of Babahoyo, with the aim of objective of analyzing the accounting data of said agency, the research aims to synthesize the profitability and the tax contribution, for which financial tools are used that allow obtaining results and carrying out an adequate comparative analysis of the last biennium, ending with a chronology of conclusions in based on the findings.